Prevalence of dental fluorosis and associated factors in schoolchildren in Cartagena, Colombia (2020)
Objectives: To describe the prevalence of dental fluorosis and associated factors related to fluoride ingestion in schoolchildren between 6 to 12 years of age in the city of Cartagena, Colombia, in 2018. Methods: A cross sectional study was performed in a sample of 142 schoolchildren in Cartagena. Sampling was a stratified random probabilistic type, selecting a proportion of schoolchildren in each locality of Cartagena. Clinical examination using Thylstrup and Fejerskov index was done to detect dental fluorosis. A structured survey was used to evaluate the associated factors (frequency of drinking water consumption, fluoridated salt, foods and beverages with high content of fluoride, and accidental ingestion of dental hygiene products). A descriptive analysis was performed for each variable calculating frequencies and proportions. Then, a bivariate analysis with Pearson's Chi-squared test and a multivariate analysis from a logistic regression with robust errors, with models adjusted by potential confounders. The significance level was fixed at 0.05. Results: Prevalence of dental fluorosis was 69.72%. Mild and moderate type of dental fluorosis were found with higher frequency, showing proportions of 62.68% and 7.04% respectively. Schoolchildren of ages 9-12-year-old were found to had 2.24 times the chance of having dental fluorosis than 6-8-year-old children (OR=2.24, 95% CI=1.02-5.03, p value=0.0472). Children who started self-brushing before the age of 3 years had 2.54 times the chance of having dental fluorosis than those who started after that age (OR= 2.54, 95% CI=1.07-6.47, p value= 0.0400). Also, those who started using mouthwashes at the age of 3 years had 77% less chance of presenting dental fluorosis than children who started before that age (OR=0.23, 95% CI= 0.05 -0.80, p value= 0.0371). Conclusions: The high prevalence of dental fluorosis in schoolchildren in Cartagena, Colombia reflects the need to design and implement effective public health programs.